Corporate governance and firm performance in China - Molnar, Margit (OECD Publishing, 2017)
A key priority in China's "new normal" period -- where returns on investment are slackening -- is corporate governance, which could lead to enhanced productivity by a better management of resources at the firm level. Corporate governance principles for listed firms follow global best practices, though their history is relatively short and the Chinese stock market has a number of features, which make the investigation of the impact of various corporate governance practices on firm performance of particular interest. Productivity is considered as a major measure of firm performance, but for comparison accounting indicators are also used to check the impact of selected corporate governance practices using firm-level data of listed firms between 1999-2015. The results are broadly in line with the existing literature: once controlling for endogeneity, there is no evidence that a greater share of independent directors boosts firm performance in general. At the time when the requirement that at least one third of directors must be independent was introduced in 2002, however, profitability improved. A greater salary gap between executives and staff hurts productivity, but boosts ROA and ROE, which are often among the objectives of executives and thus encourage them to seek short-term returns, even at the expense of productivity. While volume-based growth may lead to higher performance by the accounting ratios, it does not necessarily guarantee higher productivity. If such an expansion is debt financed, it can even harm productivity. Excessive ownership concentration appears harmful, but a certain degree of concentration may improve performance. Institutional investors, even though may own only a tiny fraction of shares, are found to boost firm performance. This Working Paper relates to the 2017 OECD Economic Survey of China (www.oecd.org/eco/surveys/economic-survey-china.htm)
Keywords: Economics; China, People's Republic